TINGKAT KELELAHAN PERAWAT DI RUANG ICU - Hammad; Rizani, Khairir; Agisti, Rinne (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2018)
Fatigue of nurses that not resolved would cause various problems. This research aims toassess the comparative level of nurse fatigue in intensive care unit of idaman banjarbaruhospital and ratu zalecha martapura hospital. This research used comparative. Thepopulation of this research were nurses of ICU in Idaman Banjarbaru Hospital as manyas 15 people and nurses of ICU Ratu Zalecha Martapura Hospital as many as 16 people,the data presented by cluster sampling; analyzed with the Mann-Whitney test. This studyshowed difference difference between level of fatigue of both hospital. The majority ofnurses fatigue in ICU RSD Idaman Banjarbaru has light fatigue while the majority ofnurses in ICU Ratu Zalecha Martapura had mild fatigue with P Value 0.015. Forhospital management must to assess the suitability of the number of nurses andworkloads to improve the service.